Integral Education with Societal Extension: Factoring Social Environment to Empower Future Generations with Holistic Human Development and Social Leadership - SAHOO, Manoj Kumar; DIVI, Sriram (Journal of Environmental Management and Tourism; Vol 14 No 3 (2023): JEMT, Volume XIV, Issue 3(67), Summer 2023, 2023)
This paper explores ways to integrate social responsibility approach to human development and analyses the feasibility of imparting social-leadership among the youth through incorporating social environment and integral teaching-learning pedagogy. The research method adopted is narrative-analytical exposition. The paper finds that co-operative rights-based approach and social responsibility approach in education can collectively create an appropriate ecosystem that can fulfill suitable developmental needs of the society and help in sustenance of development attainments.